Clinical and epidemiological features of tick-borne encephalitis in adults in Novosibirsk in 2014-2023 - Yu. V. Kazakova; Ya. S. Ulyanova; E. I. Krasnova; T. G. Burmistrova; V. G. Kuznetsova; E. N. Usolkina; V. V. Provorova; P. N. Verchenko; P. D. Urusova (Лечащий Врач, 2025)
Background. Fundamental differences in the scale, overall picture of tick-borne encephalitis, the structure and quality of its clinical variants determine the need for regular analytical work and competent dynamic accounting of clinical, epidemiological and genetic data to make coordinated decisions on the prevention, diagnosis and therapy of tick-borne encephalitis.Objective. The epidemiological and clinical manifestations of tick-borne encephalitis in adults hospitalized in the City Infectious Clinical Hospital No. 1 of Novosibirsk in 2014-2023.Materials and methods. A retrospective clinical and epidemiological analysis of 870 cases of tick-borne encephalitis in adults for the period 2014-2023, an analysis of the results of sequencing of the sequencing material of patients who died from severe tick-borne encephalitis and a retrospective assessment of the effectiveness of specific prevention measures according to data from the state reports of Rospotrebnadzor of Novosibirsk region.Results. Over the past 10 years, 870 adult patients with tick-borne encephalitis have been treated at City Infectious Clinical Hospital No. 1 of Novosibirsk. Every fifth case was characterized by the development of a focal form of tick-borne encephalitis with a severe course and high mortality (5,6 ± 0,6%). When analyzing the manifestations of the early tick-borne encephalitis period, it was revealed that the clinical forms retained the typical nature of the disease. Changes in cerebrospinal fluid are represented by two to three-digit cytosis with a predominance of lymphocytes (42%) or mixed pleocytosis. In the focal course of the disease, pleocytosis in half of the cases was polynuclear in nature. Late seroconversion was observed in 57.5% of fatal cases. According to sequencing of the sequencing material of deceased patients, in most cases, the Siberian subtype of tick-borne encephalitis was identified. Over the past 10 years, cases of tick-borne encephalitis have been reported annually among individuals receiving emergency immunoglobulin prophylaxis, of which 17% of patients subsequently developed focal forms. There were no tick-borne encephalitis vaccinees among these patients.Conclusion. The incidence rate of tick-borne encephalitis in Western Siberia remained consistently high with a predominance of forms with CNS damage, in 58.6% of those who died from tick-borne encephalitis in the Novosibirsk region, a Siberian subtype was identified. The combination of clinical symptoms of the early tick-borne encephalitis period did not allow to determine the clinical variant of the course of the disease, severity and prognosis in the first days. A reliable method of prevention of tick-borne encephalitis is vaccination, prophylactic administration of anti-tick immunoglobulin does not protect against the development of focal forms and death.